Determinants of economic growth In Sub-Saharan Africa: decomposition of exports and imports - Oyebanjo, Olawale (Research of GSB, 2018)
This dissertation examines the impact of export and import components on economic growth in 18 Sub-Saharan African countries over the period of 1995-2015. This study uses a neoclassic economic growth model containing GDP, export components, import components, export concentration index, capital and labour force as variables of analysis. The results of fixed effects estimations show that both exports and imports contribute significantly to economic growth. On a specific level, growth in raw material exports, and not manufactured exports, is significantly associated with GDP growth while growth in manufactured imports, and not raw material imports, is significantly associated with GDP growth. The export concentration index is found to have no significant relationship with GDP growth. In addition, the results find that capital formation has a more significant influence on economic growth than labour does.